A cross sectional knowledge, attitude and practice study for copper IUCD in a tertiary care centre in New Delhi - Mohapatra, Arpita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The postpartum period is one of the most sensitive period in a woman’s life. To prevent unwanted pregnancies and promote optimal interpregnancy interval, effective contraception should be discussed and offered at that time. The aim of this study was to assess the knowledge, attitude and practice of postpartum intrauterine device in antenatal patients attending OPD. Methods: A cross sectional, hospital based descriptive study was conducted from the month of September to November 2021 in the department of Obstetrics and Gynaecology in Maulana Azad Medical College, New Delhi. The total number of patients recruited in the study were 750. A total of 600 patients delivered and 150 were lost to follow up. The antenatal patients attending the OPD were provided with a structured questionnaire to assess the knowledge and attitude to copper IUCD usage. Results: Most of the patients belonged to the age group of 20-25 years. The majority of the patients were Illiterate and multigravidas (65%). Around 71% of the patients attending OPD were aware of Copper IUCD as a method of contraception. Whereas only 31% of patients were convinced of the safety of Copper IUCD. About 62% were apprehensive to use Copper IUCD. Of the 600 patients delivered in our hospital, PPIUCD was inserted in 216 (36%) patients. Conclusions: The study reveals good knowledge and favorable attitude of patients for PPIUCD as method of contraception. But it also depicts a low acceptance and usage of the same. The various reasons for this are mainly illiteracy, ignorance, social and religious taboos etc. Hence it is suggested that community education, addressing unwarranted fears of patients, incorporation of family planning in maternal and child health services etc. should be done to improve the acceptance and thereby usage of PPIUCD in patients.